Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/nar/gkaa067
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent binding to DNA and RNA facilitates the pluripotency reprogramming activity of Sox2

Abstract: Some transcription factors that specifically bind double-stranded DNA appear to also function as RNA-binding proteins. Here, we demonstrate that the transcription factor Sox2 is able to directly bind RNA in vitro as well as in mouse and human cells. Sox2 targets RNA via a 60-amino-acid RNA binding motif (RBM) positioned C-terminally of the DNA binding high mobility group (HMG) box. Sox2 can associate with RNA and DNA simultaneously to form ternary RNA/Sox2/DNA complexes. Deletion of the RBM does not affect sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 93 publications
4
52
0
Order By: Relevance
“…Based on the computational model, we predict that the interaction is mediated via the coiled-coil and SH2 domains of STAT3 and not through its DNA-binding domain, suggesting that NORAD does not compete with DNA for STAT3 binding (Figure S2D). In tune with this possibility, the SOX2 TF has been recently found to physically associate with DNA and RNA through distinct binding domains (Hou et al, 2020). Finally, we tested whether STAT3 affects the abundance of its target RNAs NORAD, SERF2, and MAD2L2.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the computational model, we predict that the interaction is mediated via the coiled-coil and SH2 domains of STAT3 and not through its DNA-binding domain, suggesting that NORAD does not compete with DNA for STAT3 binding (Figure S2D). In tune with this possibility, the SOX2 TF has been recently found to physically associate with DNA and RNA through distinct binding domains (Hou et al, 2020). Finally, we tested whether STAT3 affects the abundance of its target RNAs NORAD, SERF2, and MAD2L2.…”
Section: Resultsmentioning
confidence: 97%
“…These observations suggest that the coupling between transcription and post-transcriptional regulation may be mediated, among other mechanisms, by dual DNA-and RNA-binding proteins (DRBPs), proteins that evolved to bindDNA as well as RNA (Dvir et al, 2018;Hudson and Ortlund, 2014). Examples of such DRBPs are the pluripotency transcription factor (TF) SOX2 (Holmes et al, 2020;Hou et al, 2020) and the key regulator of chromatin architecture CTCF (Caudron-Herger et al, 2019;Kung et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A comparable number of bona-fide target factors (699 significantly modulated genes) was also identified by cDNA microarray in nasopharyngeal cancer cells [ 41 ]. This target spectrum is further expanded and diversified by interactions with RNA-based polynucleotides [ 42 , 43 , 44 ]. Accordingly, SOX2’s contributions to stemness are inherently multifactorial and are probably best described as an expression pattern shift.…”
Section: Molecular–functional Aspects Of Sox2-imposed Stemnessmentioning
confidence: 99%
“…Furthermore, our results indicated that the Ubx-HD mediates a different binding affinity compared to the full-length protein. Sox2 also mediates RNA-binding via an additional 60 amino acid RNA-binding motif (RBM) (Hou et al, 2020). Even more important, the RBM domain of Sox2 provides RNA sequence specificity as shown by SELEX experiments.…”
Section: Discussionmentioning
confidence: 99%